2019
DOI: 10.1039/c8ra08979e
|View full text |Cite
|
Sign up to set email alerts
|

Highly crystalline mesoporous SSZ-13 zeolite obtained via controlled post-synthetic treatment

Abstract: The role of remaining organics to control the extent of desilication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…This greatly improved the accessibility, but at the same time, the strength of the Brønsted acid sites decreased. Mineral acids are also used to extract Al from zeolite frameworks, while caustic solutions are used to preferentially remove Si (27)(28)(29)(30); however, these chemically selective etchants cannot be used to study the crystal growth of a zeolite.…”
Section: Introductionmentioning
confidence: 99%
“…This greatly improved the accessibility, but at the same time, the strength of the Brønsted acid sites decreased. Mineral acids are also used to extract Al from zeolite frameworks, while caustic solutions are used to preferentially remove Si (27)(28)(29)(30); however, these chemically selective etchants cannot be used to study the crystal growth of a zeolite.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the CHA zeolite is of industrial interest as a small pore zeolite due to its superiority in the particular elds of adsorption, 26,27 separation 28,29 and catalysis. 30,31 To the best of our knowledge, only one publication regarding the seed-assisted synthesis of CHA zeolite has been reported by Imai et al 32 However, no detailed characterizations have been reported thus far, particularly at the atomistic level using spectroscopic techniques such as Raman and solid-state NMR spectroscopy. These structural elucidations were required to further determine the absolute crystalline boundary out of the ternary phase diagram and understand the comparative topology in the absence of seed and/or parent gel.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the intensity of XRD reflections of the final catalysts shows lower crystallinity compared to that of the initial zeolites owing to the amorphous character of the silica binder. Furthermore, the XRD reflections also shifted toward lower 2θ, suggesting the presence of more Si-O bonds [21,22,23], which are likely due to the crystallization of some parts of the silica binder into the zeolite phase. Note that the Si-O has a shorter bond length compared to the Al-O, thus, the dspacing will be constricted, resulting in lower θ or 2θ based on the Bragg equation, nλ = 2d sin θ.…”
Section: Resultsmentioning
confidence: 99%